EFFECT AND CONSEQUENCES OF DIVORCE AMONG MUSLIM WOMEN IN KEFFI LGA OF NASARAWA STATE - Ishaq, Adam Ibrahim; Ya'aqub, Ibrahim Muhammad (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
The concept of divorce no doubt originated from the institution of marriage. And marriage is said to be the fundamental principle or practice of the society. There has been persistent cry of increasing cases of divorce in Muslim marriages on daily basis by parents, Islamic scholars; social welfare workers, the judiciary and the Keffi Emirate Council, if you go to any of our Local Courts within Keffi Local Government Area, most of the cases you find are associated with marriage. Hundreds of marriages break-up within a shortest period of wedlock. This study examines the effect of rampant divorces in Muslim community of Keffi. One of the objectives of the study was to assess the immediate effect of divorce on the Couples, children and Society. This study adopted the narrative and analytical method of research; hence both primary and secondary sources of data collection are employed in the research. The findings of this study established that as a result of divorce, most families were no longer able to manage their children’s basic needs mostly education. Societal hills arose as a result of children that were not well catered for resulting into cases like juvenile delinquency, drug abuse, hooliganism, and harlotism respectively parents should not force their children into marriage, if they do not have the natural love for each other. Parents should know that marriage is not a part time relationship, so couples should be allowed to make their choice and understand themselves better.